The development and future direction of renewable energy in Ethiopia, Kenya, Uganda, and Botswana - Girgibo, N.; Haapalainen, P.; Karita, L.; Peura, P.; Adam, G.; Sissay, T.; Worku, A.; Girma, M.; Einax, M.; Maphane, P.; Cleophas, A.; Kiprop, A.; et al. (Elsevier, 2025)
Renewable energy (RE) solutions can reduce the climate change effects and their adoption can help local villages to improve community’s energy security. This research aims to identify the challenges and future development paths for African nations based on practical project experience and a systematic literature review. This will help researchers and others (such as policymakers) to implement national and international projects in Africa RE development. The literature and project experience show, the main challenges noticed in Africa are 1) resistance to change and lack of acceptance of RE by local communities; 2) the prohibitive cost of RE technologies and a lack of financial supports and insurance; 3) a lack of knowledge/knowledge gaps in RE production and management; 4) limited willingness and knowledge to share data and lack of knowledge in the energy consumption by locals and no available weather data; 5) a lack of RE infrastructure; 6) the difficulty of establishing contacts with locals; and 7) security issues. The significance and novelty of this research lie in identifying the practical challenges faced by locals and international organizations when implementing RE projects in African nations; providing recommendations for possible solutions and the future direction of African RE development; and planning international continuous collaboration through the creation of a collaborative network. The Energy Village concept was helped Finland and one case study is Jeppo biogas plant, which is build based on this concept and its projects. Despite the numerous challenges facing the development of RE in Africa, African nations hold significant untapped RE potential that can be harnessed systematically. The challenges noticed can be reduced by using the recommended solutions described in this article.
Keywords: Renewable energy; Energy Village; LEAP-RE; Africa project challenges; Future RE direction; Policy implications; fi=Markkinointi|en=Marketing|